FOREIGN EXCHANGE OPERATIONS OF COMMERCIAL BANKS AND THEIR CLASSIFICATION (Marketing Journal, 2025)
The article examines the classification and improvement of currency operations in commercial banks to enhance banking efficiency. It substantiates the need for risk management, effective resource allocation, and automation of operations based on currency p olicy, international experience, and national legislation. Practical recommendations are provided for introducing competitive foreign exchange services and developing strategic approaches tailored to customer needs. 363
Keywords: commercial bank; currency operations; currency policy; banking strategy; financial security; international settlements; banking risks